THE CORRELATION BETWEEN STUDENTSâ€™ VOCABULARY MASTERY AND THEIR ABILITY IN WRITING HORTATORY EXPOSITION TEXT - Ajeng, Galuh Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This research was a descriptive quatitative study that focuses on the correlation between studentsâ€™ vocabulary mastery and their ability in writing hortatory exposition text. The problem formulation of this research was â€œis there any correlation between studentsâ€™ vocabulary and their writing ability of hortatory exposition text?â€. Whereas the objective of this research were to know and to describe whether or not there is the correlation between studentsâ€™ vocabulary mastery and their ability in writing hortatory exposition text. The sample of this research was 28 students of fourth grade semester of STKIP PGRI Bandar Lampung. This research was taken place in STKIP PGRI Bandar Lampung. After calculating by using Product Moment formula the writer got rxy was 0.54. rcount = 0.54 was taken place between 0.400 â€“0.600. rtable for significance level 5% is 0.374 andit an be concluded that rcount = 0.54 is higher than rtable = 0.374. So Ho is accepted and Ha is rejected. It means that there is a fair correlation between studentsâ€™ vocabulary mastery and their ability in writing hortatory exposition text at the fourth semester of English Department of STKIP PGRI Bandar Lampung in 2016/2017.